2007
DOI: 10.3732/ajb.94.9.1527
|View full text |Cite
|
Sign up to set email alerts
|

Polyploidy and self‐fertilization in flowering plants

Abstract: Mating systems directly control the transmission of genes across generations, and understanding the diversity and distribution of mating systems is central to understanding the evolution of any group of organisms. This basic idea has been the motivation for many studies that have explored the relationships between plant mating systems and other biological and/or ecological phenomena, including a variety of floral and environmental characteristics, conspecific and pollinator densities, growth form, parity, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
181
1
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(194 citation statements)
references
References 86 publications
7
181
1
5
Order By: Relevance
“…The first is that there is a general trend toward self-fertilization in polyploids (Barringer, 2007) and autogamy is often proposed as one of the catalysts for a widespread distribution or successful colonization (Baker, 1955). However, the trend is not clear for the Asteraceae, which has sporophytic self-incompatibility (SSI).…”
Section: Discussionmentioning
confidence: 99%
“…The first is that there is a general trend toward self-fertilization in polyploids (Barringer, 2007) and autogamy is often proposed as one of the catalysts for a widespread distribution or successful colonization (Baker, 1955). However, the trend is not clear for the Asteraceae, which has sporophytic self-incompatibility (SSI).…”
Section: Discussionmentioning
confidence: 99%
“…Histological studies of post-pollination events of apomictic self-compatible neopolyploid species of Bignoniaceae do not show endosperm malformations that could be caused by inbreeding depression (Bittencourt & Moraes 2010;Sampaio et al 2013a), although a slight delay in endosperm development, which is commonly associated with the action of the LSI, has been reported in Anemopaegma acutifolium (Sampaio et al 2013a). In addition, inbreeding depression is not expected to occur in neopolyploids such as H. serratifolius, especially allopolyploids, which can avoid inbreeding problems due to high rates of heterozygosity (Barringer 2007, Husband et al 2008.…”
Section: Discussionmentioning
confidence: 99%
“…Although neopolyploidy seems to be effectively associated with the breakdown of self-incompatibility systems, especially the gametophytic system (de Nettancourt 1977;Richards 1986;Levin 2002;Pannell et al 2004;Barringer 2007), some studies suggest that the self-fertility found in these pseudogamic apomictic sporophytic species is not determined exclusively by neopolyploidy (Oliveira et al 1992;Bittencourt & Semir 2005;Bittencourt & Moraes 2010;Sampaio et al 2013a). The LSI found in most species of Bignoniaceae allows pollen tube growth, ovule penetration, fertilization and endosperm development prior to self-pollinated pistil abscission (Bittencourt et al 2003;Bittencourt & Semir 2005;Gandolphi & Bittencourt 2010).…”
Section: Introductionmentioning
confidence: 99%
“…polyploids resulting from genome duplication) are also found to be parthenogenetic. Note that polyploidy is also a frequent feature of selfing plants [50].…”
Section: (A) a Marginal Habitat?mentioning
confidence: 99%